PENYINGKAPAN CITRA PEREMPUAN CERPEN MEDIA INDONESIA: KAJIAN FEMINISME - Juanda Juanda; Azis Azis (Center of Language and Cultural Studies, 2018)
One of the female phenomena which was authored by the authors short stories in Media Indonesia is the narrative of oppressed women. The purpose of this study is to explore the image of women in short stories in the Media Indonesia. This research is descriptive qualitative research that focuses on the image of women. The approach used in this research is the feminism approach. The data were analysis techniques using heuristic and hermeneutic techniques. The results of the study indicate that there are various negative treatments experienced by women. The author used the short stories as a representation of their images through the Media Indonesia daily. Women's image is manifested in the form of physical image, psychic, helpless, resigned to the situation, housewife, loyalty, child guard, domestic, husband's companion, and social.